Bridging the gap between intention and execution: effective tree planting practices in Manhattan, Kansas - Saunders, Gabrielle (Kansas State University, 2024)
Trees provide ecological, social, health, and economic benefits in urban and suburban environments. These include stormwater management, improved perception of safety, shade, and carbon sequestration. The realization of these benefits is contingent on trees growing to their full maturity and the overall wellness of trees. Tree planting ordinances in urban design often call for a certain number of trees for each new development, but design practices and the maintenance needed to keep trees alive often fall short. Young, vulnerable trees planted in harsh environments may only survive a few years past planting, while large, established trees are removed from sites to make way for future development. As trees die due to their surrounding conditions, projected benefits—why they were required and planted—are foregone completely and cities fall short in reaching climate action goals and creating healthy living environments. Insufficient attention is being paid to the implementation and maintenance strategies needed to keep the trees alive and thriving — past the establishment period — in order to actualize their benefits. This study aims to identify those strategies, and how to implement them effectively as high-density residential zoning districts densify from single-family homes to multi-family complexes. Several methods were used to answer the following question: As two sites in Manhattan, Kansas are densified, how can street trees be implemented and maintained to maximize their longevity and receive the full benefits they can provide, based on their contextual and biophysical conditions? Three precedent study reviews are followed by an analysis of residential blocks that have experienced densification and significant tree loss in the last 10 years. Projective designs show how innovative planting strategies can be applied to two sites. Planting design guidelines for future development, including site design essentials, tree planting drawings, and required implementation and maintenance strategies, will help ensure tree health past the establishment period. Design guidelines applied to two sites in Manhattan, Kansas (which have yet to be densified, but have a potential to be based on their zoning classification and contextual patterns of the neighborhoods they belong to) will help the City of Manhattan and Kansas Foresters as they review development proposals. This study builds upon past research and practices to identify when specific planting design, implementation, and maintenance strategies must be applied, and provides a framework that can be used in Manhattan, Kansas and other densifying urban landscapes.
Keywords: Implementation; Tree mortality